Endurance training for judo athletes: Improving anaerobic and aerobic capacity in the high altitude - Purnamasari, Ira; Novian, Geraldi; Febrianty, Mona Fiametta; Rismayadi, Alen (UIR Press, 2024)
Background Problems: Judo is a sport that requires aerobic and anaerobic abilities. This is because the scoring in judo matches is different from other martial arts, where athletes will look for absolute 'ippon' points in one match. Therefore, training is needed that can support increasing aerobic and anaerobic capacity in judo athletes. Endurance training at high altitudes is a training method that is believed to have benefits for athletes' aerobic and aerobic capacity. Research Objectives: The study aims to examine the effect of endurance training on increasing the anaerobic and aerobic capacity of judo athletes based on the Special Judo Fitness Test (SJFT), which is a specific test for the sport of judo that can describe anaerobic and aerobic fitness according to the needs of judo. Methods: This research was conducted in the Puncak area of West Java, which is included in the highlands. An experimental method was used in this research on twenty-four Indonesian elite judo athletes who are carrying out training camps to face the SEA Games in Vietnam in 2021. The t test using SPSS Version 24 was used for data analysis in this study. Findings and Results: The results showed that there was a significant increase in anaerobic and aerobic capacity at high altitudes in judo athletes, as seen from the SJFT. Conclusion: This study concluded that endurance training could increase the anaerobic and aerobic capacity of judo athletes in the highlands. Endurance training at high altitudes for judo athletes is highly recommended because it has been proven to have a significant effect on increasing anaerobic and aerobic capacity. We recommend that judo coaches carry out training at high altitudes because it has been proven to improve the aerobic and anaerobic abilities of judo athletes.